Analisis Manajemen Program Bahasa Arab pada Lembaga Pendidikan Formal di Indonesia - Lola Hervina H; Nuril Mufidah; Abdul Malik Karim; Nofa Isman; Asbarin Asbarin (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Arabic language program management has been widely applied to formal education in Indonesia, however, there are differences and similarities in program management in actuating between one formal institution and another. For this reason, the objectives of this study are to describe the differences in Arabic language program management; to describe the similarities of Arabic language program management; to analyze Arabic language program management at in terms of actuating (objectives, approaches and strategies, methods, materials and learning resources, as well as class division). This research uses library research with descriptive method. The results of this study are the similarities of formal educational institutions, namely in the objectives, although there are innovations from the institutions themselves, methods, and class divisions; the differences are in the methods, materials, and approaches and strategies used; the objectives namely: GBPP there are also those who adopt from other institutions, approaches and strategies using teacher-centred only and on teachers and students, methods mostly use the tarjamah grammatical, reading, memorization, and others, on learning materials and resources using books which was printed by the founder and based on Arabic subjects, and the class division was only two divisions (the ula class and the wustho class).